Using structural equation modeling in the understanding of functional disability in older adults - Darlene Mara dos Santos Tavares; Nayara Gomes Nunes Oliveira; Flavia Aparecida Dias Marmo; Joilson Meneguci
Objective: to analyze functional disability and its associated factors among community-dwelling older adults. Method: a cross-sectional study, conducted with 1,635 older adults distributed in the following age groups: 60 to 69, 70 to 79, and 80 years old or more, living in a health macro-region of the state of Minas Gerais. Descriptive and trajectory analysis was carried out (p<0.05). The parameters were estimated by the Maximum Likelihood method. Results: the highest percentage was female, with a monthly income of 1 minimum wage and living with a companion. In the age groups from 60 to 69 and from 70 to 79 years old, older adults with a partner predominated; and, among those aged 80 years old or more, widowed individuals prevailed. In the three groups, functional disability occurred hierarchically. Lower schooling, frailty and depressive symptomatology were factors directly associated with functional disability in the advanced activities; frailty and sedentary behavior were directly associated with functional disability in the instrumental activities. In the older adults aged between 60 and 69 years old and from 70 to 79 years old, sedentary behavior was associated with greater dependence on the basic activities. Conclusion: the expanded understanding of the factors in the functional disability of the older adults, according to age group, helps the health professional in the development of preventive measures for this disease.